Protecting the Antarctic Environment: Will a Protocol be enough? - Ijaiya, Hakeem Olasunkanmi (NIU Journal of Humanities, 2018)
The Antarctica as a single continent, with no indigenous or permanent human inhabitants, and no commercial or industrial activities, is more easily governed by a single comprehensive environmental treaty regime known as the Antarctic Treaty System (ATS). These include the Antarctic, the Agreed Measures for the Conservation of Antarctic Fauna and Flora, the Convention for the Conservation of Antarctic Seals, the Convention for the Conservation of Antarctic Marine Living Resources, the Convention on the Regulation of Antarctic Mineral Resource Activities, and the Protocol on Environmental Protection to the Antarctic Treaty (The Madrid Protocol). The Madrid Protocol was designed to protect and preserve the Antarctic environment. This paper assesses the Madrid Protocol. The Protocol on Environmental Protection to the Antarctic Treaty (Madrid Protocol)